Associations between procrastination, personality, perfectionism, self-esteem and locus of control. Issue 3 (27th May 2017) - Boysan, Murat; Kiral, Erkan
ABSTRACT: To date, many variables but particularly trait-like psychological constructs have been found to strongly contribute to procrastination but the complex relations among these variables collectively have received almost no attention. The purpose of the study was to provide a more profound understanding of the relations between procrastination, perfectionism, big five personality, locus of control and self-esteem. Young adults (162 women, 80 men: M  = 20.98) completed measures of academic procrastination, self-esteem, big five personality, perfectionism and locus of control. Parental criticism was a significant correlate of procrastination, while personality traits of conscientiousness, agreeableness and organisation were inversely associated with procrastination behaviour. These findings suggest that personality-based intervention approaches with the inclusion of family can be more influential in procrastination prevention and treatment.